Extracellular vesicle-mediated cellular crosstalk in lung repair, remodelling and regeneration. (26th January 2022) - Kadota, Tsukasa; Fujita, Yu; Araya, Jun; Ochiya, Takahiro; Kuwano, Kazuyoshi
The unperturbed lung is highly quiescent, with a remarkably low level of cell turnover. However, once damaged, the lung shows an extensive regenerative capacity, with resident progenitor cell populations re-entering the cell cycle and differentiating to promote repair. This quick and dramatic repair response requires interactions among more than 40 different cell lineages in the lung, and defects in any of these processes can lead to various lung pathologies. Understanding the mechanisms of interaction in lung injury, repair and regeneration thus has considerable practical and therapeutic implications. Moreover, therapeutic strategies for replacing lung progenitor cells and their progeny through cell therapy have gained increasing attention. In the last decade, extracellular vesicles (EVs), including exosomes, have been recognised as paracrine mediators through the transfer of biological cargo. Recent work has revealed that EVs are involved in lung homeostasis and diseases. In addition, EVs derived from specific cells or tissues have proven to be a promising cell-free modality for the treatment of lung diseases. This review highlights the EV-mediated cellular crosstalk that regulates lung homeostasis and discusses the potential of EV therapeutics for lung regenerative medicine. Extracellular vesicles are important intracellular mediators in lung repair, remodelling and regeneration, and are potential therapeutic agents for lung regenerative medicine https://bit.ly/3jhc7sb